Pendekatan Psikologis Dalam Upaya Manajemen Konflik Agama - Mercy W.K Waney; Mariana Lusye Marlyn Lausan; Gabriela Rantung (Institut Agama Kristen Negeri Manado, 2021)
ABSTRACT: This study uses a descriptive qualitative approach. The purpose of this study is to find out how the psychological approach of religion in conflict management efforts. In religious life, living in peace is a very important part. Even though it is realized that religion is often used to show radicalism and intolerance. Religion, which is universal in nature, is understood as a concept, experience and actualization of espoused values. Religion is expected to provide a solution to the problems of the soul of its adherents because the values contained include mutual respect and respect. Through a religious psychology approach, we can see the resolution of a conflict.